Speciation of heavy metals in sludge from electroplating industry / Noorhazlina Binti Abu Bakar - Abu Bakar, Noorhazlina (2013)

(untitled)
Application of sequential extraction method to environmental samples provides relevant information about possible toxicity, mobility, and bioavailability of heavy metals when they are discharged into the environment. The concentration of heavy metals in three electroplating sludge samples (two samples from Zn electroplating industries and one sample from Ni electroplating industry) and potential of mobility based on its association form were studied. BCR sequential extraction method was used to fractionate the metal content into acid soluble/exchangeable, reducible and oxidizable fractions. Residual and total metal content were determined in aqua regia digest. The extract were analysed for metals using inductively coupled plasma mass spectrometry (ICP-MS). Zn concentration was found to be the highest in the samples collected from zinc electroplating industries (145.9 and 187.7 g kg-1) as compared to that of nickel electroplating industry (0.6 g kg-1). The descending order of the average total metal contents for these three samples were Zn>Ni>Fe>Cr>Pb>Cd. From the sequential extraction, Cd, Zn and Ni were found more frequently in acid soluble/exchangeable fraction, showed its susceptibility to be leached easily. The oxidizable form is dominant for all the three samples studied. Also, Fe and Pb extracted were higher in residual fraction. Due to the higher total Zn and Ni concentrations and its high mobility, the investigated sludges should be disposed off into landfill after stabilization to prevent the leaching of metals to the surrounding area.